Impacts of Pre-Retirement Guidance and Family Involvement on Retirement Adjustment of Retirees in Nigeria - O.O. Olatomide (University of Sofia, 2017)
The study examined retirement adjustment of teacher-retirees in Osun State, and explored the interaction effects of pre-retirement guidance and family in-volvement on retirement adjustment. Exposit-facto design was used. The population comprised retirees from public, civil and private establishments from which 122 teacher-retirees were selected using a multi-stage sampling technique. An instrument: Family Involvement, Pre-retirement Guidance and Retirement Adjustment Questionnaire was used for data collection. Three research questions and three hypotheses guided the study. Data were analyzed using descriptive and inferential statistics. Results revealed that retirees in Osun State are not optimally adjusted, and positive significant interaction effect was found between family involvement and pre-retirement guidance on retirees adjustment, among others. Appropriate policy implications are outlined.